Role of hydrogen and hydrogen storage in lithium hydride - Lamichhane, Saran; Giri, Mahesh (Journal of Lumbini Engineering College, 2023)
Tight binding linear muffin-tin orbitals atomic sphere approximation have been used to examine the structural stability, electronic properties, charge density and magnetization of lithium hydride (LiH). In our study, the direct band gap (4.25 eV) detected between the valence bands (especially dominated by hydrogen) and conduction bands implies that LiH is insulating in nature with strong ionic bonds and weak orbitals-hybridization. Furthermore, we noticed that the hydrogen contributed more to the total density of states than the lithium in the complete system, based on the spin polarised partial density of states of H and Li. Because our calculated band gap accords with experiment, the results found in LiH suggest that it is a better choice for optoelectronic devices. The strength of hybridization of orbitals and band gap properties improve energy storage as well.